Research and Development of a Vulvar Moisturizer to Target Unmet Gynecological and Aesthetic Needs - Krychman, M; Zahr, AS; Kononov, T (Journal of sexual medicine, 2022)
There is a limited number of peer-reviewed medical publications concerning non-invasive topically genital cosmetic products that could act as a frontline treatment for aesthetic concerns. The vulvar area has received limited research and attention in both the cosmetic and skincare industry. Many topical creams exist primarily as medical interventions; however, topical cosmetic products are an unmet consumer need in that they have less risk than surgical intervention when seeking enhancement or improvement of the female genital appearance. The unmet consumer need can be realized with a non-invasive vulvar moisturizer developed to improve vulvar aesthetics. A novel vulvar moisturizer product (VMP) was formulated and tested in a  prospective study that was conducted to assess consumer acceptance and tolerability of the VMP when used by healthy women twice-daily for the duration of four weeks. A VMP was formulated by a multi-disciplinary team including an Obstetrician / Gynecologist, Cosmetic Chemist, and Chemical Engineer. The formulation delivery system includes a reverse emulsion containing emollients (jojoba esters), antioxidants (vitamin C and vitamin E), skin protectants (dimethicone), and moisturizing ingredients, including but not limited to Hyaluronic acid. This novel cream contains technology to allow for immediate and prolonged skin soothing and moisturization. Clinical testing was performed. An institutional review board (IRB)-approved single-center consumer in-use study that was performed at a USA based sexual medicine center by a trained sexual medicine physician. Twenty-five female subjects, 18-85 years old, and in good medical and gynecological health with no active untreated medical conditions were recruited for this study. Subjects applied the VMP on both the left and right sides of the external vulvar tissue twice daily for four weeks. At the completion of the study, subjective tolerability measurements and self-assessment were completed. A binomial exact test was performed on responses to each question. The null hypothesis was that the responses (positive, negative, neutral) were evenly distributed (33%, 33%, 33%) among the 25 subjects. The goal was to disprove the null hypothesis at a statistical significance of *p <0.05. The novel VMP successfully completed 12-weeks of accelerated stability in final packaging testing and meet shelf-life criteria during research and development. After termination of formal stability testing, the product was submitted for clinical testing. Twenty-five, female subjects, with an average age of 39 +/- 10 years completed the consumer in-use study. Female subjects were primarily Caucasian (48%) and 44% Hispanic or Latino completed the study. Self-assessment results indicated highly statistically (***p < 0.001) favorable responses for each category: vulva perception, product characteristics, product package, and overall satisfaction. Specifically, after 4 weeks: - 100% of subjects responded favorably to “After product use, my vulva feels soft.” - 100% of subjects responded favorably to “This product nourishes vulvar skin.” - 96% of subjects responded favorably to “After product use, my vulva feels overall healthy and beautiful.” - 96% of subjects responded favorably to “This product maintained and improved my natural healthy vulvar skin.” Overall, the subjects felt confident and valued that the VMP was formulated with high-quality ingredients and reported appreciation for a non-hormonal product. Results from subjective tolerability evaluation showed the VMP yielded no vulvar burning, itching, or stinging, or any other adverse events for any subject by the end of the study. This single-center consumer in-use study supports the hypothesis that the VMP when used twice daily for four weeks achieved consumer acceptance and was tolerable. Consumer acceptance was demonstrated in all self-assessment categories, vulva perception, product characteristics, packaging, and overall satisfaction. Further research is currently being conducted with the VMP for a post shave utilization use. Commercialization of this vulvar moisturizer and availability is anticipated in 2023. Yes, this is sponsored by industry/sponsor: Revision Skincare®